2010
DOI: 10.2118/132440-pa
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Data Analysis and Dynamic Fracture Modeling Key To Understanding Complex Waterfloods: Case Study of the Pierce Field, North Sea

Abstract: The performance of many waterfloods [and enhanced-oil-recovery (EOR) schemes] is characterized by fluid injection under fracturing conditions. Especially when the geology is complex and the mobility of the reservoir is low, induced fractures can be of the same order as the well spacing, which has a significant (in general undesired) impact on both areal sweep and vertical conformance. Therefore, fluid injection needs to be actively managed and surveyed in order to design an appropriate injection strategy over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…This triggered an integrated study with the objective of understanding the observations and formulating remedial actions for the short term (water/gas injection optimization) to medium/long term (e.g., infill drilling of producers/injectors). Early results of this study, focusing on the producer-injector pair in the east, have been reported in Hustedt and Snippe (2010). Their model results suggested that tensile (and possibly also shear) fractures grow from the water injector in a direction roughly orthogonal to the salt/sediment interface, i.e., also toward the producer wells.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…This triggered an integrated study with the objective of understanding the observations and formulating remedial actions for the short term (water/gas injection optimization) to medium/long term (e.g., infill drilling of producers/injectors). Early results of this study, focusing on the producer-injector pair in the east, have been reported in Hustedt and Snippe (2010). Their model results suggested that tensile (and possibly also shear) fractures grow from the water injector in a direction roughly orthogonal to the salt/sediment interface, i.e., also toward the producer wells.…”
Section: Introductionmentioning
confidence: 74%
“…1). The pair in the east (A8z-A1) was covered in Hustedt and Snippe (2010). By applying the same methodology (as described in Hustedt and Snippe and summarized in the following) on the other producer/injector pair, we have learned that qualitatively all pairs behave the same in terms of induced fractures.…”
Section: Fig 11-maximum Shear Stress Based On Geomec-computed Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors reported integrating surveillance data with full-field simulation studies. Some of these studies include those of Hustedt and Snippe (2010), Langaas et al (2007), Bahar et al (2005), and King et al (2002), among others over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…The method consists of analyzing the pressure transient signal produced when shutting the well. Especially when repeated periodically in the same well, PFO testing provides valuable information on injection performance and in-situ mobility changes, as well as on formation properties, boundaries etc (Hustedt and Snippe 2010).…”
Section: Introductionmentioning
confidence: 99%